Productivity of traditional trade smes in Northwestern Mexico - Beltrán Lun, Zugey Enriqueta (2025)
The traditional channel plays a fundamental role in the economy, as it comprises businesses that serve as a key source of employment and market dynamism. However, Small and Medium-sized Enterprises (SMEs) operating within this channel face various challenges that can impact their productivity and competitiveness. In this context, the present study aimed to identify the factors limiting the productivity of SMEs in the traditional channel in the Municipality of Cajeme, located in northern Mexico. A descriptive, non-experimental, quantitative, and cross-sectional study was conducted. Data was collected from 158 companies through an online survey consisting of 33 questions, and the generated information was analyzed using SPSS software version 24. The main findings indicate that productivity in the traditional channel is negatively affected by the lack of continuous improvement practices, absence of process formalization, insufficient infrastructure, limited market knowledge, and inadequate administrative equipment. Additionally, the loss of market positioning has been driven by product and service diversification and the incipient use of technology. It is recommended that businesses adapt to current technological advancements and improve their service quality and efficiency to meet consumer demands effectively.